APPLICATION OF STATISTICAL METHODS TO THE STUDY OF THE SPATIO-TEMPORAL EVOLUTION OF THE PHYSICO-CHEMICAL PARAMETERS OF THE SURFACE WATERS OF THE CHERF WADI BASIN. ALGERIA - Bellazi, M. A; Zenati, N; Belahcene, N; Berredjem, Y; Gheid, A. E (university of el oued/جامعة الوادي, 2021)
The physico-chemical parameters of the surface waters of the Cherf wadi watershed experience considerable variations over space and time under the influence of natural or anthropogenic phenomena. The application of the Kruskal-Wallis test for the comparison of the physico-chemical parameters showed that there were very significant intersite differences for pH, electrical conductivity, bicarbonate, chloride and sodium; as well as significant differences between the dates for all the studied variables. The typology highlighted by principal component analysis and Hierarchical Classification Analysis is linked to the availability of mineral elements by the anthropic activities of variable intensity depending on the sites, is added a natural process of mineralization related to the contact water- rock and throughfall phenomena. Statistical processing also revealed two types of water. The first type represents waters with very strong mineralization with very high sodium and chloride values characterizing the waters of site 5. The second type is marked by strong mineralization with high contents of Calcium. It characterizes the sites receiving discharges coming respectively from certain agglomerations not connected to the wastewater system and from the treatment plant.
Article
Keywords: Discharge, Watershed, Mineralization, Spatio-temporal variablity.